Seismic behavior and strength capacity of steel coupling beam-to-SRC wall joints. (15th December 2019) - Ji, Xiaodong; Cheng, Yuhao; Leong, Tongseng; Cui, Yao
Highlights: Full-scale tests were conducted on steel coupling beam-to-SRC wall joints. The steel coupling beam-to-SRC wall joints failed in panel shear mode. The capacity designed joint had slight damage upon to failure of steel beam. Design model for calculating the nominal joint strength is presented. Mechanism and accuracy of design model are validated by test data and FE analysis. Abstract: A hybrid coupled wall system, where steel coupling beams couple steel reinforced concrete (SRC) walls in series, has been recognized as an alternative to reinforced concrete (RC) coupled wall systems for enhanced seismic performance of high-rise buildings. A key issue of this system is seismic design of steel coupling beam-to-SRC wall joints. This paper presents a series of full-scale tests to investigate the cyclic behavior and strength capacity of the steel coupling beam-to-SRC wall joints, where a steel beam was rigidly connected to an encased steel column in wall boundary using a fully welded connection detail. The steel beam-to-SRC wall joints failed in panel shear mode, characterized by yielding of the steel web panel and joint transverse reinforcement, and crisscrossed-diagonal cracking and crushing of joint panel concrete. A design model for calculating the nominal strength of the steel beam-to-SRC wall joint is presented. The accuracy of the design model was verified against the collected test data and additional finite element (FE) analysis. The experimental tests and FE analysis also identified that severe vertical cracks might develop along the inner side of wall boundary element, due to horizontally tensile forces induced by the steel beam flange. Increased amount of horizontally distributed rebar is recommended to be assigned in around the join region, in order to control such unwanted damage. In addition, the test results of one specimen demonstrated that properly designed beam-to-wall joint remained slightly damaged when the steel coupling beam fully developed its plastic rotation.